Original paperLeflunomide in treatment of rheumatoid arthritis patients - Rell-Bakalarska, Maria; Rutkowska-Sak, Lidia; Kwiatkowska, Małgorzata; Lisowska, Barbara; Wojtecka-Łukasik, Elżbieta; Maśliński, Sławomir (Reumatologia/Rheumatology, 2007)
The aim of this study was to investigate the effectiveness and safety of leflunomide in the treatment of rheumatoid arthritis (RA). Therapy with leflunomide was performed on 276 patients with active RA, defined by a disease activity score (DAS). All patients had previously been given conventional drug treatment without positive effects. The mean duration of leflunomide treatment was 16 months. Adverse events related to leflunomide therapy were evaluated. Before and after treatment, the serum activity of cartilage enzymes (NAH-ase and NTPPH-ase) was normal. The efficacy of leflunomide was shown in 70% of cases. This therapy proved ineffective in approximately 13% of patients. The results of this study demonstrated that leflunomide treatment had to be discontinued in 18% of patients because of adverse effects.